2021
DOI: 10.1002/qj.3969
|View full text |Cite
|
Sign up to set email alerts
|

Extreme precipitation events over northern Italy. Part II: Dynamical precursors

Abstract: The connection between weather extremes and Rossby wave packets (RWP) has been increasingly documented in recent years. RWP propagation and characteristics can modulate the midlatitude weather, setting the scene for temperature and precipitation extremes and controlling the geographical area affected. Several studies on extreme precipitation events (EPEs) in the Alpine area reported, as the main triggering factor, a meridionally elongated upper‐level trough as part of an incoming Rossby wave packet. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…From the results of this study alone, however, it is not straightforward to compare our findings to the existing literature on cloud-radiative feedback on storm tracks. Most importantly, cloud-radiative effects on extratropical storm tracks are more complex than by direct upperlevel PV modification (Grise et al, 2019). The lack of variation with the baroclinic life cycle found herein hinges on the continued existence of a wavy upper-level pattern.…”
Section: Downstream Moist-baroclinic Developmentmentioning
confidence: 67%
See 1 more Smart Citation
“…From the results of this study alone, however, it is not straightforward to compare our findings to the existing literature on cloud-radiative feedback on storm tracks. Most importantly, cloud-radiative effects on extratropical storm tracks are more complex than by direct upperlevel PV modification (Grise et al, 2019). The lack of variation with the baroclinic life cycle found herein hinges on the continued existence of a wavy upper-level pattern.…”
Section: Downstream Moist-baroclinic Developmentmentioning
confidence: 67%
“…The longwave radiative tendency is largely constant during the baroclinic life cycle of both ridges and troughs. Because this tendency makes a contribution to the amplitude evolution comparable to the advective tendencies, and due to the large recent interest in cloud-radiative feedback on extratropical storm tracks and on cyclone evolution (e.g., Schäfer and Voigt, 2018;Grise et al, 2019;Papavasileiou et al, 2020), we investigate the radiative tendency in some more detail. Figure 10 depicts the spatial pattern of this tendency (orange contours).…”
Section: Downstream Moist-baroclinic Developmentmentioning
confidence: 99%
“…This surface cyclone facilitates not only warm‐air advection poleward of the Arctic Circle but also the formation of a corridor of enhanced precipitable water that extends zonally across the North Atlantic. In this sense, anomalously strong North Atlantic jet events resemble the large‐scale flow evolution associated with atmospheric river events impacting Western Europe (e.g., Lavers and Villarini, 2013; Pohorsky et al ., 2019; Grazzini et al ., 2020) and have the potential to negatively influence the state of the cryosphere via the wind stress and low‐level warm‐air advection (e.g., Woods et al ., 2013; Liu and Barnes, 2015; Woods and Caballero, 2016; Papritz, 2020) induced by the southeast Greenland cyclone. Further investigation into the relationship between anomalously strong North Atlantic jets and downstream impacts over Western Europe and the cryosphere would be a worthwhile endeavor.…”
Section: Discussionmentioning
confidence: 99%
“…The southeast Greenland cyclone also transports anomalously warm air poleward of the Arctic Circle. Therefore, the translation of jet events across the North Atlantic establishes a large‐scale environment capable of inducing precipitation events across Western Europe (e.g., Lavers and Villarini, 2013; Pohorsky et al ., 2019; Grazzini et al ., 2020) and impacting the state of the cryosphere poleward of the Arctic Circle (e.g., Woods et al ., 2013; Liu and Barnes, 2015; Woods and Caballero, 2016; Papritz, 2020).…”
Section: Jet Event Development and Evolutionmentioning
confidence: 99%
“…Mastrantonas et al (2021) demonstrated that a clustering combination of sea level pressure (SLP) and geopotential height at 500 hPa (Z500) increases the conditional probability of EPEs by more than a factor of 3, which could be critical for extended-range forecasts. Grazzini et al (2021) further investigated the relation between EPEs and Rossby wave packets (RWPs), showing the evolution and properties of precursor RWPs to be key for the categorization of EPEs. Despite the improved understanding, the accuracy of forecasts is still insufficient to adequately assess the timing, location, and intensity of rainfall and flash flooding in certain situations, which is a key step towards prevention and mitigation.…”
Section: Introductionmentioning
confidence: 99%